2009
DOI: 10.1080/14999011003635670
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Forensic Service Delivery System for Juveniles Adjudicated Incompetent to Stand Trial

Abstract: Our study examines the experiences of 563 youth ordered into restoration services after a judicial finding of adjudicative incompetence. Among this group, 72% were determined to be restored to competence usually within 90 to 120 days of services provided in the least restrictive environment allowed by the courts. These outcomes were achieved using an individualized psycho-educational intervention that combined intensive case management, developmentally informed interactive educational tools, and case integrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 13 publications
1
20
0
Order By: Relevance
“…The results showed that young adults aged < 20 years had the highest rate of restoration (at 74%) in an average of 46.6 days. This high rate of restoration is consistent with three studies of juvenile restoration, which found a restoration rate of 71–76% in an average of 90–120 and 217 days (McGaha, Otto, McClaren, & Petrila, 2001; Warren et al., 2010, 2019). The notable difference is that this JBCT study achieved the same rate of restoration in a fraction of the time.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The results showed that young adults aged < 20 years had the highest rate of restoration (at 74%) in an average of 46.6 days. This high rate of restoration is consistent with three studies of juvenile restoration, which found a restoration rate of 71–76% in an average of 90–120 and 217 days (McGaha, Otto, McClaren, & Petrila, 2001; Warren et al., 2010, 2019). The notable difference is that this JBCT study achieved the same rate of restoration in a fraction of the time.…”
Section: Discussionsupporting
confidence: 88%
“…-85 programs that provide intensive daily treatment with both individual and multiple group-based rehabilitative activities, while limited programs (coded as "L") are constrained to one-to-one counseling in the jail on a lessthan-daily frequency. In rough chronological order of implementation, these JBCT programs include Virginia (F: 1997-2002; L: since 2011), Louisiana (L since 2007); Arizona (four Fs: county programs starting in 2003 in Maricopa, 2007 in Pima, and2010 in Yavacai and Yuma counties); California (12 Fs: starting in 2011 in San Bernardino County); Georgia (F: since 2011 in Fulton County); Colorado (F: since 2013); Washington (two Fs: since 2015); Minnesota (L: since 2015); Utah (L: since 2015); Wisconsin (L: since 2016); Texas (F: in development since 2017); Pennsylvania (F: authorized in 2018, not implemented) and Tennessee (L: years unknown). Florida has attempted mental health diversion programs for ISTs since 1999 (Florida Substance Abuse and Mental Health Corporation and Florida Partners in Crisis, 2009).…”
Section: The Context For the Growth Of Jbctmentioning
confidence: 99%
“…As noted earlier, McGaha et al () analyzed data for all youths adjudicated incompetent and referred for competence remediation in specialized secure facilities in Florida during a three‐year period. Warren et al () reported on over 500 youth in Virginia's program, which accomplishes its juvenile incompetence remediation services while youth are in the community or in detention centers. Several results were similar for the two studies.…”
Section: Ac Evaluations Of Juvenilesmentioning
confidence: 99%
“…Warren et al. () examined the restoration outcomes of 563 youth referred by the courts for restoration services in Virginia. After receiving an average of 61 to 90 days of services, 73 percent of youth were determined to be competent.…”
Section: Introductionmentioning
confidence: 99%
“…Warren et al. () found that the highest rate of achieved competence was among youth who were not mentally ill or mentally retarded (91 percent) and the lowest rate of achieved competence was among youth with mental retardation (47 percent). In Florida, McGaha, Otto, McClaren and Petrila () examined over 400 youth deemed incompetent to stand trial (excluding youth transferred to adult court or considered incompetent because of developmental immaturity) and referred for restoration services.…”
Section: Introductionmentioning
confidence: 99%